Dilemmas of China's growth in the Twenty-First Century - Song, Ligang (ANU Press, 2012)
Since economic reforms began in 1978, China has been a focal point for observing the effects of market liberalisation. China has not only truly become one of the 'emerging giants' in the world economy but also provided a successful example for transition from a centrally-planned to a market economy. Thus, there is a keen interest about what lies ahead for such a significant economic player. Dilemmas of China's Growth in the Twenty-First Century is a comprehensive treatment of China's economic achievements to date and prospects for the twenty-first century. Covering topics as diverse as economic stability and growth sustainability, WTO membership and its implications, income disparity, agricultural policy, trade and investment prospects, Dilemmas of China's Growth in the Twenty-First Century is a powerful work and essential guide to the latest trends and prospects for the Chinese economy.